CASH WAQF INVESTMENT AND POVERTY ALLEVIATION: CASE OF TABUNG MASJIDS IN MALAYSIA - Hasan, Rashedul; Hassan, M. Kabir; Rashid, Mamunur (Journal of Islamic Monetary Economics and Finance, 2018)
Recent investigations of the financial management practices of mosques in Indonesia have influenced this study, which investigates the ability of mosques in Malaysia to invest cash waqf for development activities. The impact of cash waqf investment is further extended to study the importance of such cash waqf donations toward poverty alleviation. 100 mosques in Melaka and Terengganu are selected for the purpose of conducting a survey using a self-developed questionnaire. Data collected from the survey are tested for their validity and reliability before conducting Structural Equation Modelling (SEM) analysis using Smart PLS 3.0. This study finds that cash waqf donation plays a positive role in increasing the ability of the selected states to alleviate poverty. The negative relationship between cash waqf investment and donation raises the need for a rigorous analysis. A conceptual model integrating cash waqf investment, donation, and poverty alleviation is provided in this study, which is the first of its kind. The results provided by the study will allow regulators and mosque fund managers to understand the significance of cash waqf donations and the importance of effective cash waqf management. Efficient investment of cash waqf can ensure sustainable and perpetual income that will allow a mosque to play a vital role in improving the living standards of the Muslim Ummah. The findings of the study cannot be generalized for all states in Malaysia due to the limitation of purposive sampling.